Sorghum pathology and biotechnology - a fungal disease perspective: Part I. Grain mold, head smut, and ergot - Little, Christopher R.; Perumal, Ramasamy; Tesso, Tesfaye T.; Prom, Louis K.; Odvody, Gary N.; Magill, Clint W. (My University, 2011)
Three common sorghum diseases, grain mold, head smut and ergot, each of which is directly related to seed production and quality are covered in this review. Each is described with respect to the causal organism or organisms, infection process, global distribution, pathogen variability and effects on grain production. In addition, screening methods for identifying resistant cultivars and the genetic basis for host resistance including molecular tags for resistance genes are described where possible.
Citation: Little, C., Perumal, R., Tesso, T., . . . & Magill, C. (2012). Sorghum Pathology and Biotechnology - A Fungal Disease Perspective: Part II. Anthracnose, Stalk Rot, and Downy Mildew. European Journal of Plant Science and Biotechnology, 6(1), 31-44. http://www.globalsciencebooks.info/Online/GSBOnline/images/2012/EJPSB_6(SI1)/EJPSB_6(SI1)31-44o.pdf
Keywords: Sorghum; Grain mold; Head smut; Ergot